A novel act‐and‐wait control scheme for fixed‐time stabilization of input‐delay systems and assignment of the monodromy matrix. (3rd November 2021) - Zhang, Zhe; Zhou, Bin; Michiels, Wim; Yang, Xuefei
Abstract: An act‐and‐wait (AAW) fashioned control scheme is proposed for input delay systems, which is characterized by switches between different gains during the acting phases. Under very mild conditions, the novel control scheme allows to freely assign the monodromy matrix and to solve the fixed‐time stabilization problem. In additionally, a variant is proposed where the control law is simplified by keeping the control signal constant after every switch, amendable for a sampled‐data implementation. For multi‐input systems it is also demonstrated how the number of switches per acting period in the basis scheme can be reduced to the dimension of the system, starting from the controllability indices set. The effectiveness of the proposed methods is verified on two simulation case‐studies.